Empowerment Model of Rural Cattle Breeders in Livestock Waste Management (Case Study in the village of Waturejo, Ngantang, Malang Regency) - Siswantoro, Ajik; Yuliati, Yayuk (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2017)
Livestock activities in rural areas are often less concerned with good waste management. It is noted that one adult cow can produce 15-25 kg of dung per day. With the number of cattle population reaching 14,140 heads, the cattle dung collected per day amounts to 353.5 ton. If the waste of cattle dung is not properly utilized, it can have a serious impact on people health and cause environmental pollutions. This research was aimed to understand how community activities were run in utilizing and managing the waste of cattle dung and to formulate models of community empowerment in the waste management of cattle dung. This research used a qualitative approach. The determination of informants was conducted by way of snowball sampling while the data analysis used the model of Miles and Huberman. The results of the research in the field found that the community was still not maximal in the waste utilization of cattle dung. In contrast, the community preferred to dispose of the waste instead of utilizing it into manure or organic fertilizer. The effort of making biogas reactor has not been able to help the community utilize the waste maximally. As an effort to protect the environment from the great deal amount of cattle dung, a model of Rumah Pupuk Masyarakat (RPM) – Community's Fertilizer House – was formed in order to overcome the problem of cattle dung, which has not been maximized properly in the site of the research.